Engineering confederalism for Iraq - Khan, Shamsul; Kirmanj, Sherko (Taylor & Francis Group, 2015)
This article examines Iraqi political developments in the last few years. It argues that unless a constitutional mechanism for proper dispersal of political powers across Iraq's regions and branches of its government is developed quickly, it may become too late for defeating Islamic State in Iraq and Syria, stemming the sectarian and ethnic conflicts, overcoming its perpetual crises of governance or for keeping Iraq united. We suggest that a con federal structure is a better and lasting political solution for Iraq than federal or other structural configurations.We also argue that power-sharing and consensus must be intertwined directly into the constitutional fabric of the political structure.